Are the Patterns of Cytomegalovirus Viral Load Seen After Solid Organ Transplantation Affected by Circadian Rhythm?. (20th February 2022) - Rafferty, Hannah; Murray, Matthew J; Tam, Jerry C H; Macfarlane, Alastair; Smith, Colette; Lumley, Sheila F; Atabani, Sowsan; McKeating, Jane A; Sharma, Dinesh; Reeves, Matthew; Whitmore, David; Griffiths, Paul
Abstract: Background: Cytomegalovirus (CMV) is an important opportunistic pathogen after transplantation. Some virological variation in transplant recipients is explained by donor and recipient CMV serostatus, but not all. Circadian variability of herpesviruses has been described, so we investigated the effect of time of day of transplantation on posttransplant CMV viremia. Methods: We performed a retrospective analysis of 1517 patients receiving liver or kidney allografts at a single center from 2002 to 2018. All patients were given preemptive therapy with CMV viremia monitoring after transplantation. Circulatory arrest and reperfusion time of donor organ were categorized into 4 periods. Patients were divided into serostatus groups based on previous CMV infection in donor and recipient. CMV viremia parameters were compared between time categories for each group. Factor analysis of mixed data was used to interrogate this complex data set. Results: Live-donor transplant recipients were less likely to develop viremia than recipients of deceased-donor organs (48% vs 61%; P < .001). After controlling for this, there was no evidence of time of day of transplantation affecting CMV parameters in any serostatus group, by logistic regression or factor analysis of mixed data. Discussion: We found no evidence for a circadian effect of transplantation on CMV viremia, but these novel results warrant confirmation by other centers. Abstract : Using a large data set on preemptive cytomegalovirus therapy for solid-organ transplant recipients, we found no association between time of day of transplantation and cytomegalovirus viremia but found increased viremia in recipients of deceased-donor compared with live-donor transplants.